Software package "COMPOSITE-2D" and its use for calculating the stress-strain state of different ensembles of inclusions in elastomeric composites and their effective properties - Evlampieva, Svetlana Evgenievna; Parkaeva, Ekaterina Aleksandrovna; Svistkov, Aleksandr Lvovich (Computational Continuum Mechanics, 2013)
We have developed a software package "COMPOSITE-2D" for calculating the stress-strain state of elastomeric composites containing hundreds of spherical inclusions (plane problem) and their effective properties. Structural stresses and strains at any given point of the material are evaluated using the theory of functions of a complex variable. Comparison is made between the results of calculations for the ensemble of regular inclusions obtained by the software package "COMPOSITE-2D" and the numerical solution for the periodicity cell obtained by a standard formulation of the finite element method. An example of calculation of the relationship between the effective modulus of elasticity and the degree of reinforcement of the system by solid inclusions is presented.